FORMACIONES SOCIOECONÓMICAS DE TRABAJO Y EL TRABAJO DEL CONSUMO - Glucksmann, Miriam (Sociología del Trabajo, 2012)
Developments in global work and employment, and the ensuing complexity of contemporary connections and divisions of labour, raise questions about the adequacy of the foundational concept of the division of labour to confront new realities. The aims of this paper are first to initiate a process of revitalisation, and second, to propose a new research terrain of ‘consumption work’, as part of the process of renewal. A multi-dimensional framework is proposed in order to analyse the varied dimensions of differentiation and interdependence of labour that comprise overall socio-economic formations of labour. Inclusion of the consumer is integral to this re-conception, and a preliminary definition and characterisation of consumption work is also sketched.